Pelatihan Public Speaking Upaya Peningkatan Kemampuan Komunikasi Bagi Calon Duta Kampus di Politeknik Negeri Cilacap - Somantri, Oman; Perdana Wanti, Linda (ISAS (Indonesian Society of Applied Science), 2023)
Limitations of someone's ability to communicate in public places become an obstacle for everyone. A student, especially a campus ambassador is required to have good communication ability, therefore the information conveyed can be received by all parties. To overcome the problems faced by prospective campus ambassadors, in this article an activity is proposed in the form of public speaking training for Campus Ambassador nominees at the Cilacap State Polytechnic. The training is carried out using the lecture and role-play method. The stages of the activity are carried out through several stages, namely the stages of planning, implementing, and evaluating. The results of the training have a significant impact on the level perception of knowledge of the trainees with an average of 70% understanding of the material presented.